Analisis Faktor-Faktor yang Memengaruhi Terjadinya Hipertensi pada Pasien Rawat Jalan di Puskesmas Belawan - Rismadi, Kiki (Universitas Haji Sumatera Utara, 2025)
The study methodology used is a quantitative approach employing a cross-sectional design. The study was carried out at the Belawan Health Center. The group consists of a total of 7,615 persons, resulting in an average of approximately 760 patients per month. The sample selection in this study was carried out with the Slovin formula, which yielded a total of 100 respondents. The research findings suggest that the occurrence of hypertension in outpatients at the Belawan Health Center is influenced by excessive alcohol intake, smoking behaviors, obesity, and physical activity. Obesity is the primary factor that has the most significant impact on the occurrence of hypertension in outpatients at the Belawan Health Center. The obesity conditions observed in the research participants can be attributed to factors such as being in the premenopausal stage, insufficient physical activity including a lack of regular exercise, unhealthy eating habits characterized by high fat consumption, and inadequate intake of balanced nutrition. The Belawan Community Health Center should organize regular sports programs that are specifically designed for hypertensive patients with obesity. Exercise can be accomplished by engaging in aerobic activities that entail fundamental movements. In addition, exercise recommendations can be submitted to the Health Service for obtaining bicycles that can serve as exercise equipment for hypertension patients who are obese. Additionally, it is possible to create standard operating procedures (SOPs) to execute internal suggestions that engage nutrition officers in overseeing the nutritional well-being of hypertension patients with obesity. These recommendations can help explore the correlation between the various components of food intake and obesity. Likewise, internal recommendations can include including reproductive health professionals in addressing female hypertension patients who have become obese as a result of pre-menopausal circumstances.